Indonesian Army Strategic Communication Against Social Media Disinformation - Rasdiana Rasdiana; Alem Febri Sonni; Muhammad Akbar (JURNAL EKOLOGI BIROKRASI, 2026)
This study examines the strategic communication practices implemented by the Indonesian Army, particularly through the Military Education and Science Center (Pusdik Pengmilum) under the Army Doctrine, Education, and Training Command (Kodiklatad), in countering disinformation and hoaxes circulating on social media. Employing a qualitative approach, data were collected through in-depth interviews, observations, and document analysis involving communication personnel, instructors, and institutional leaders. The findings reveal that strategic communication is implemented through systematic planning, multi-channel media utilization, audience-centered messaging, and the integration of informative, persuasive, and participatory communication approaches. The institution employs owned media, earned media, and shared media, supported by multimedia content, storytelling, counter-narratives, and digital analytics to enhance audience engagement and strengthen institutional credibility. Communication effectiveness is supported by competent human resources, technological infrastructure, interorganizational collaboration, leadership commitment, organizational learning, and public trust. However, several challenges remain, including the rapid diffusion of misinformation, limited human resources, uneven digital literacy, technological constraints, fragmented audience attention, and declining trust in institutions. Overall, the study demonstrates that strategic communication serves not only as an instrument for information dissemination but also as a mechanism for strengthening digital literacy, safeguarding information integrity, and enhancing organizational resilience against evolving information threats in the digital era.